2016
DOI: 10.1073/pnas.1601355113
|View full text |Cite
|
Sign up to set email alerts
|

PI3K-resistant GSK3 controls adiponectin formation and protects from metabolic syndrome

Abstract: Metabolic syndrome is characterized by insulin resistance, obesity, and dyslipidemia. It is the consequence of an imbalance between caloric intake and energy consumption. Adiponectin protects against metabolic syndrome. Insulin-induced signaling includes activation of PI3 kinase and protein kinase B (PKB)/Akt. PKB/Akt in turn inactivates glycogen synthase kinase (GSK) 3, a major regulator of metabolism. Here, we studied the significance of PI3K-dependent GSK3 inactivation for adiponectin formation in diet-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 71 publications
(85 reference statements)
0
30
0
Order By: Relevance
“…Dyslipidemia is another hallmark of MS, which is characterized by high serum TG levels and a high LDL/HDL ratio . In this study, TBTCl exposure resulted in profound lipid‐elevating effects in mice.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Dyslipidemia is another hallmark of MS, which is characterized by high serum TG levels and a high LDL/HDL ratio . In this study, TBTCl exposure resulted in profound lipid‐elevating effects in mice.…”
Section: Discussionmentioning
confidence: 62%
“…To characterize the responsiveness of TBTCl‐exposed‐mice to insulin, we determined P‐AKT (Thr308 and S473) in liver tissue and skeletal muscle isolated from the mice at 8 min after insulin injection . The total AKT abundance was not different between the TBT groups and the control (Figure A‐C).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Gsk-3 is a major regulator of cellular metabolism, and has been linked to obesity via its role in regulating the insulin/PI3K pathway. Interestingly, it was recently found that transgenic mice expressing a form of Gsk-3 that is insensitive to inhibition by PI3K signaling were protected from developing metabolic syndrome, which includes obesity (75). While it is not yet known if the role of FTO in obesity is connected to Gsk-3 activity and mRNA methylation levels, it is a tantalizing possibility that should be explored further.…”
Section: Discussionmentioning
confidence: 99%